Being and Becoming in Nyāya-Vaiśeṣika - Šileikis, Saulius (Acta Orientalia Vilnensia, 2004)
The article aims at analysing the semantics of Sanskrit verbs denoting being and becoming and their influence on the development of philosophical thinking, in particular the ontology of Nyāya-Vaiśeṣika. It is argued that in Sanskrit the durative aspect of the verb asti resulted in the development of the qualificative meaning of the present participle sat and the qualitative abstracts satt̄a and sattva. The process reached its peak in the concept sattva of Sāṃkhya philosophy. In Nyāya-Vaiśeṣika sat preserved its durative existential meaning, and its derivatives sattā and astitva comprised the positive reality as universals. In the negative description of reality the verb bhavati and its derivative abhāva prevailed, and this fact conditioned the development of the dynamic and concrete conception of absence. As a consequence, Nyāya-Vaiśeṣika created neither the universal concept of non-being nor the concept of empty space.